The Effect of Financial Literacy on MSME Performance Through Access to Financing Products and Financial Risk Attitude: A Study on Padang Restaurant MSMEs in Bandung City - Intan Maharani Putri Setiawan; Mohammad Rizal Gaffar; Sherry Novalia Fujiasti (JURNAL AKUNTANSI DAN MANAJEMEN, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play an important role in the economy of Bandung City. However, they continue to face challenges related to financial management, access to financing products, and financial risk-related decision-making. This study aims to analyze the effect of Financial Literacy on MSME Performance through Access to Financing Products and Financial Risk Attitude as mediating variables. This study employed a quantitative approach with an explanatory research method. Primary data were collected by distributing questionnaires to 155 owners or managers of Padang restaurants in Bandung City selected using a purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results indicate that Financial Literacy has a positive and significant effect on MSME Performance, Access to Financing Products, and Financial Risk Attitude. Access to Financing Products and Financial Risk Attitude also have positive and significant effects on MSME Performance. Furthermore, Access to Financing Products and Financial Risk Attitude significantly mediate the effect of Financial Literacy on MSME Performance, indicating partial mediation. These findings demonstrate that Financial Literacy can improve MSME Performance both directly and indirectly through enhanced access to financing products and a more measured attitude toward financial risk. The findings are expected to provide practical considerations for MSME owners, financial institutions, and the government in supporting the performance improvement of Padang restaurant MSMEs in Bandung City.